Menumbuhkan Kesadaran Lingkungan Melalui Edukasi Sampah Di Dusun Cemare, Desa Lembar Selatan, Kabupaten Lombok Barat - Nabila, Hesti; Fadhillah, Falya Aura; Sesareny, Nadiya; Sur’atunisa, Dean; Seftiana, Irma; Suyantri, Eni; Setiawan, Heru (Universitas Mataram, 2025)
Waste is one of the most pressing environmental problems and challenges in Indonesia, especially in coastal areas. One of the areas facing this problem is Cemare Hamlet in South Lembar Village, West Lombok Regency. Waste Education can be one of the solutions in dealing with waste problems from an early age. Waste education activities carried out by Thematic KKN students aim to instill awareness about environmental cleanliness from an early age to children. The methods used in the waste management education program in Cemare Hamlet include field observations, preparation and implementation of waste education activities, management of plastic waste and clean up activities. The results of waste education activities in Cemare Coastal Literacy show a positive impact on children's understanding and concern for the environment. Waste management activities produce creative waste magazines with the theme of protecting the environment that utilize waste such as bottle caps, plastic food wrappers, used paper, and straws. Waste education activities in Cemare Hamlet succeeded in raising children's awareness about the importance of keeping the environment clean. This initiative shows that structured environmental education can have a positive impact in shaping environmental care behavior from an early age.